Imobilização da lipase tipo B de Cândida antarctica em sílica macroporosa e polimetilmetacrilato visando a síntese do oleato de etila - Matos, Leonardo José Brandão Lima de (2014)
Immobilization of enzymes provides advantages such as increased in: stability, level of process control, yield and purity of the final product, in addition to allowing the use of different reactor configurations. In this study, two types of support, an organic polymer (polimetilmetacrilato- PMMA) and other inorganic (silica) were used for the immobilization of lipase Candida antarctica type B (CALB). Different alcohols (ethanol, iso-propanol, n-butanol) were evaluated as agents for optimization of the immobilization process, the concentrations of 5, 10 and 15% (volume of alcohol × 100 / solution volume immobilization). Immobilization of PMMA was conducted using two different protocols here denominated first and second protocol generation. The best results of hydrolytic activity and esterification to the derivative of the first generation was 3,91 ± 0,09 UpNPB/g. of catalyst e 409,5 ± 19,7 Uoleic acid/g. of catalyst, respectively. When using the protocol of the second generation, the best results were obtained when aa immobilization was carried out in the presence of 5% Triton® X-100 2 mM, rising rate of the esterification reaction between the derivatives studied was highly significant with a higher ratio of 3,81 times to the derivative prepared with Triton® X-100. The CALB was also immobilized for the macroporous silica support (IB S60S® - Chiralvision), the activate agent used was Triethoxy(octyl)silane (C8-TEOS). The results observed for immobilization in the presence of 5% n-butanol were the best for both hydrolytic activity, being four times higher than the activity for the immobilized derivative without alcohol, as for the esterification activity was 985,1 ± 5,6 Uoleic acid/g. of catalyst . All observed derivatives supported on silica and PMMA reached a level conversion for equilibrium esterification reaction for a reaction time of 24 h the best results varying between 80 to 90%.